Shifting roles of public relations professionals in artificial intelligence technology era: Case study of XY PR and digital agency - Erna Febriani; Guntur Eko Saputro; Riedho Dharmawan; Shellie Paola Chelsie (Jurnal Aspikom, 2025)
The Artificial Intelligence (AI) technology has changed the way public relations professionals conduct research, build relationships with the public and personalize messages, one of which is at the PR and Digital XY agency. Artificial intelligence is not only a tool but also a technology that drives a shift in the role of Public Relations professionals in the communications industry. This study aims to analyze how the shift in the role of public relations professionals in dealing with the development of artificial intelligence technology in the public relations profession. The theory used is McLuhan's technological determinism and the role of Dozier and Broom's public relations. The method used in this study is a case study with data collection techniques in the form of interviews and literature studies. The results of the study show that in the era of artificial intelligence, there has been a shift in the role of public relations professionals from the four conventional PR roles to the role of gatekeepers and validators. PR is required to have digital communication competencies and ethical behavioral principles in using artificial intelligence technology.